Relationship between the level of self-esteem and attitudes towards domestic violence of nursing students - Banu Tufan Koçak; Nihal Ünaldı Türkkan; Arzu Kader Harmancı Seren (Association of Nurse Managers, 2014)
OBJECTIVE: Level of self-esteem and attitudes towards domestic violence of nursing students has importance because of they are going to be expected to work in health facilities where the victims of violence refers to. This study was performed with the purpose of defining the level of self-esteem and attitudes towards domestic violence of nursing students who are studying in a nursing college. METHODS: The study is descriptive and cross sectional. All the nursing students in the nursing college were included to the study without sampling. Written permission was obtained for the study from the management of the nursing college. 412 surveys were got from the participants and were analyzed. Data were collected by Personal Information Form, Coopersmith Self-esteem Inventory and Attitudes Scale Towards Domestic Violence. In analyzing of data, frequency and Pearson correlation tests were used. RESULTS: Average self-esteem point of nursing students was found 35.98+-7.57; and attitude point of them towards domestic violence was determined as 25.23+-8.75. It was found negative, poor and significant correlation (r: -0.234, p: .000) between the level of self-esteem and attitudes towards domestic violence of nursing students. CONCLUSION: It can be said that the self-esteem level of nursing students is generally high and their attitudes towards domestic violence is negative.